The Use of New Technologies in Multicultural Team Management in Times of Covid-19 - Małgorzata Nadziakiewicz (Communications of International Proceedings, 2021)
This article develops a theoretical framework for the use new technologies in multicultural team management. The purpose of this article is to present the importance of migration flows for the team’s management in the organization. Migrations affect the economy, economic relations and the labor market. Modern corporations give employment to workers from different cultural and ethnic backgrounds, and this involves many challenges. There are presented methods of cooperation and how is possible to improve efficiency in  the Multicultural Teams and the Virtual Teams. In the times of covid-19, the Multicultural and Virtual Teams are playing important role in organizations. Thanks to new technologies, people all around the world can work from their homes.
Keywords: Multicultural Team Management; Virtual Teams; Intercultural Communication; New Technologies; Pandemic of Covid-19